2021
DOI: 10.4081/hr.2021.8361
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Hemostatic Parameters and Mortality Rate in Patients with Non-Small Cell Lung Cancer

Abstract: The increasing level of hemostatic parameters and tumor markers were associated with cancer progression and poor prognosis, particularly in NSCLC. The objective of this study is to determine whether there was a correlation between hemostatic parameters and mortality rate in patients with NSCLC. This was a prospective analytical study with a pretest-posttest design which included 41 patients with diagnosis of NSCLC. Plasma levels of PT, APTT, TT, D-dimer, and fibrinogen were measured before initiation of chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Fib was high in patients with advanced and poorly differentiated LSCC. Accordingly, it was reported that Fib is elevated in various malignancies, including colorectal, lung, breast, and gastric [26, 37,38]. Moreover, we found that Fib increased more signi cantly in LSCC patients with poor differentiation, lymph node metastasis, neurovascular invasion, and advanced LSCC.…”
Section: Discussionsupporting
confidence: 58%
“…Fib was high in patients with advanced and poorly differentiated LSCC. Accordingly, it was reported that Fib is elevated in various malignancies, including colorectal, lung, breast, and gastric [26, 37,38]. Moreover, we found that Fib increased more signi cantly in LSCC patients with poor differentiation, lymph node metastasis, neurovascular invasion, and advanced LSCC.…”
Section: Discussionsupporting
confidence: 58%
“…cells to release procoagulant products (19). This can be also one of the potential targets for cancer detection in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, APTT is one of the routine indexes of hemostatic examination for surgical patients, the optimal cutoff value for APTT time was 34 S with a sensitivity of 60.6% and a specificity of 72.12% ( 18 ). Tumor cell products presented on their surface or substances secreted in the microenvironment may either directly trigger clotting system activation or indirectly trigger it by stimulating extravascular host cells to release procoagulant products ( 19 ). This can be also one of the potential targets for cancer detection in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The association between malignancy and disturbances in the haemostasis balance has been studied for almost two centuries [ 18 ]. In recent years, a large number of researchers have reported a significant role of both coagulation and fibrinolytic parameters in the pathogenesis of several cancers as prognostic and predictive indicators of survival and future clinical outcomes [ 19 ]. There is much evidence indicating that components of the haemostatic system contribute to the fundamental aspects of tumour biology, such as angiogenesis, metastasis, cancer progression and modulation of immune responses [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%